Efficient File-Naming Convention for Data Exchange in Construction Industry - Pasalski, Jędrzej; Owerko, Tomasz; Kasznia, Dariusz; Wrzosek, Maciej; Rochel, Maciej; Czerw, Kamil (Geomatics and Environmental Engineering, 2025)
This paper aims to find common and universal naming convention for files to allow for the efficient exchange of data within the construction industry. Since building information management (BIM) has become a norm on the market and new technologies are rapidly driving the concept, there is a noticeable lack of unification in the deliveries of projects. The analysis focuses on exploring the most common naming conventions that have been mostly defined in the national standards and explores the widely adopted British National Annex 2 to BS EN ISO 19650-2:2018. Part of this research is a survey that was undertaken among professionals to understand the needs and habits that are related to file-naming. Furthermore, the ergonomics, comfort of use, and information capacity of the naming system were examined. Based on all of these, the authors suggest an optimal file-naming convention for building construction projects, which should help the industry in efficiency gains. In the future, there is the potential of developing a form to define project needs at the very start or tools for checking naming compliance with a proposed structure.